Precise strategies for selecting probiotic bacteria in treatment of intestinal bacterial dysfunctional diseases - Yang, Jiajun; Qin, Shunyi; Zhang, Hao (Frontiers in Immunology, 2022)
Abundant microbiota resides in the organs of the body, which utilize the nutrition and form a reciprocal relationship with the host. The composition of these microbiota changes under different pathological conditions, particularly in response to stress and digestive diseases, making the microbial composition and health of the hosts body interdependent. Probiotics are living microorganisms that have demonstrated beneficial effects on physical health and as such are used as supplements to ameliorate symptoms of various digestive diseases by optimizing microbial composition of the gut and restore digestive balance. However, the supplementary effect does not achieve the expected result. Therefore, a targeted screening strategy on probiotic bacteria is crucial, owing to the presence of several bacterial strains. Core bacteria work effectively in maintaining microbiological homeostasis and stabilization in the gastrointestinal tract. Some of the core bacteria can be inherited and acquired from maternal pregnancy and delivery; others can be acquired from contact with the mother, feces, and the environment. Knowing the genera and functions of the core bacteria could be vital in the isolation and selection of probiotic bacteria for supplementation. In addition, other supporting strains of probiotic bacteria are also needed. A comprehensive strategy for mining both core and supporting bacteria before its clinical use is needed. Using metagenomics or other methods of estimation to discern the typically differentiated strains of bacteria is another important strategy to treat dysbiosis. Hence, these two factors are significant to carry out targeted isolation and selection of the functional strains to compose the resulting probiotic preparation for application in both research and clinical use. In conclusion, precise probiotic supplementation, by screening abundant strains of bacteria and isolating specific probiotic strains, could rapidly establish the core microbiota needed to confer resilience, particularly in bacterial dysfunctional diseases. This approach can help identify distinct bacteria which can be used to improve supplementation therapies.